THE EFFECT OF PUNISHMENT AND EMPLOYEE DISCIPLINE ON EMPLOYEE WORK ACHIEVEMENT AT BANK SULUT TOMOHON - Salawati, Vicaria Susana (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
One of the job performance aspects is about work achievement. This measurement is used common by every company to evaluate, either one or overall all employees productiveness in the company which is related with the company existence. Work achievement is something you really work hard to do it well and accomplishing it successfully. This research is conducted in Bank Sulut Tomohon.  Research objectives are to know the effect of punishment and employee discipline on employee work achievement. This research uses causal type of research where it will investigate the influence of punishment and employee discipline on employee work achievement at Bank Sulut Tomohon. Using a multiple regression model to answer the research problem. The population observed is 45 employees that work In Bank Sulut Tomohon. Results and conclusions are the effect of punishment and employee discipline has not simultanously significant influence on employee work achievement, then partially punishment have significant influence on employee work achievement but partially employee discipline have positive but not significant influence for employee work achievement at Bank Sulut Tomohon. Management Bank Sulut Tomohon should recruit capable and qualified employee to contribute the achievement of the company. Keywords: work achievement, punishment, employee discipline